2006
DOI: 10.1016/j.bbrc.2006.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Release of FGF1 and p40 synaptotagmin 1 correlates with their membrane destabilizing ability

Abstract: Fibroblast growth factor (FGF)1 is released from cells as a constituent of a complex that contains the small calcium binding protein S100A13, and the p40 kDa form of synaptotagmin (Syt)1, through an ER-Golgi-independent stress-induced pathway. FGF1 and the other components of its secretory complex are signal peptide-less proteins. We examined their capability to interact with lipid bilayers by studying protein-induced carboxyfluorescein release from liposomes of different phospholipid (pL) compositions. FGF1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 45 publications
2
40
0
Order By: Relevance
“…However, FGF-1, a close relative of FGF-2, has been proposed to be able to acquire a so-called molten globule conformation that might allow the protein to penetrate membranes (Prudovsky et al, 2003). Interestingly, FGF-1 has been suggested to destabilize membranes through its ability to interact with acidic membrane lipids (Graziani et al, 2006). Biochemical studies using chemically defined liposomes to reconstitute FGF-2 membrane translocation in vitro as well as genome-wide RNAi screening procedures to identify gene products (e.g.…”
Section: Fgf-2 Targeting and Membrane Translocation -A Speculative Hymentioning
confidence: 99%
“…However, FGF-1, a close relative of FGF-2, has been proposed to be able to acquire a so-called molten globule conformation that might allow the protein to penetrate membranes (Prudovsky et al, 2003). Interestingly, FGF-1 has been suggested to destabilize membranes through its ability to interact with acidic membrane lipids (Graziani et al, 2006). Biochemical studies using chemically defined liposomes to reconstitute FGF-2 membrane translocation in vitro as well as genome-wide RNAi screening procedures to identify gene products (e.g.…”
Section: Fgf-2 Targeting and Membrane Translocation -A Speculative Hymentioning
confidence: 99%
“…[17][18][19][20][21] Such studies often quantitate CF release but do not compare the results with the transport of other species. In several studies of the SAT family of transporters developed in our lab, we have used carboxyfluorescein release to assay anion transport through vesicular bilayers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Sanz and Gallego showed that aFGF exhibits high lipid binding affinity at acidic pH (32). We have recently demonstrated that the mutations of specific lysine clusters in aFGF and p40 Syt1 result in a significant decrease of their ability to destabilize liposomes composed of acidic phospholipids and a dramatic inhibition of their non-classical release from the cells (33). Bychkova et al, investigating the structure of cytochrome c under acid conditions, suggested that the negative membrane potential creates an acidic microenvironment that in-turn causes a denaturation effect on proteins, leading to their partial unfolding (34).…”
mentioning
confidence: 97%